Pengaruh Iklan Media Sosial, Electronic Word of Mouth dan Citra Merek Terhadap Keputusan Pembelian Smartphone Oppo: Studi Kasus pada Pengguna Smartphone OPPO di Yogyakarta - Atikah; Fitroh Adhilla; Zunan Setiawan (Masyarakat Ekonomi Syariah Bogor, 2025)
The increasing functionality of smartphones during the Covid-19 pandemic has driven higher production to meet the growing demand for online activities. This study examines the influence of social media advertising, electronic word of mouth (eWOM), and brand image on purchasing decisions for OPPO smartphones in Yogyakarta. Using a quantitative approach, the study involved 150 respondents, with validity and reliability tests conducted using r-table and Cronbach’s Alpha (α > 0.60). Hypothesis testing was performed using multiple linear regression analysis, including the F-test for simultaneous influence, the t-test for partial influence, and the coefficient of determination (R²) to assess the variation in the dependent variable. The results show that social media advertising, eWOM, and brand image significantly influence purchasing decisions. Social media advertising (X1) has a positive effect with a regression coefficient of 0.509, eWOM (X2) has the strongest influence with 0.578, and brand image (X3) has a positive impact with 0.430. The F-test results indicate a significant simultaneous influence, with an R² value of 0.523, meaning that 52.3% of purchasing decisions are explained by these three variables, while the remaining 47.7% is influenced by other factors not examined in this study.